A combination of different mass spectroscopic techniques for the analysis of dynamic changes of histone modifications - Bonaldi, Tiziana; Imhof, Axel; Regula, Jörg T. (Proteomics (Weinheim), 2004)
The N‐terminal tails of the histones are subject to many enzyme‐mediated post‐translational modifications, such as lysine acetylation, lysine and arginine methylation, serine phosphorylation, poly‐ADP ribosylation and the attachment of the small peptide ubiquitin. These modifications, singly or in combination, are thought to generate an epigenetic code that specifies different patterns of gene activity. We present a detailed study on the mapping of histone post‐translational modifications using a combination of matrix‐assisted laser desorption/ionization‐time of flight and electrospray ionization tandem mass spectrometry analysis of peptides generated by protease cleavage of individual histones isolated from different developmental stages. Due to their high content in basic amino acid residues and in order to be able to quantitatively compare two different samples we developed a chemical derivatization protocol. This strategy enabled us to determine the primary sequence of the peptides and to unambiguously assign specific modifications. This method is generally applicable to histone samples from various sources and can be used to study changes of modification patterns during early embryonic development or tissue differentiation and regeneration.